Analysis of the evolution of the objective arbitrability of the intra-corporate disputes over the shareholders’ resolutions in Germany - Chyla, Łukasz (Studia Iuridica Toruniensia, 2017)
The subject of this article is the thorough analysis of the evolution of the objective arbitrability of corporate disputes under German law. The German legal system, which was initially very opposite to any liberal approach towards arbitration, has lately undergone substantial changes which led to broad arbitrability of intra-corporate disputes regarding challenging the shareholder’s resolutions. The latest German liberal approach is the consequence of the widespread opinion that corporate arbitration constitutes the best alternative to mis7t and fossilized system of the regular courts. The aim of the article is to present the newest practical solutions as well as doctrinal controversies that still stand in a way of full recognition of the arbitration courts’ jurisdiction over the corporate disputes. This paper also deeply analyzes the role of the DIS (German Institution of Arbitration) as well as its corporate regulations DIS-SRCoLD (DIS Supplementary Rules for Corporate Law Disputes).